Analisis Jejaring Konflik Petani Tembakau Kabupaten Temanggung - Ritaningrum; Atika Wijaya (IAIN Madura, 2023)
Conflict in society is a social phenomenon that originates from relations between individuals who have mutual interests but have conflicting viewpoints that cause conflict. The conflict between tobacco farmers in Campurejo Village is a phenomenon that is no longer surprising because tobacco plants are often called controversial plants from time to time. The purpose of this study was to analyze the conflict network of tobacco farmers in Campurejo Village, Temanggung Regency because conflict is a routine phenomenon every year during the tobacco season. This study used descriptive qualitative research methods supported by observation, interviews, and literature studies. The results show that the conflict with tobacco farmers in Campurejo Village occurs because there are many interested actors, namely the government, tobacco factories, middlemen, and laborers. The government is a gateway for farmers to issue policies to tighten the reduction of tobacco production under the pretext of health. This is inversely proportional to the large number of tobacco imports which has caused the price of local tobacco to shift. The trading system for tobacco is considered chaotic so tobacco farmers are said to be the losers because the trade system policies are not in favor of the welfare of farmers. Keywords: Network Analysis, Farmer Conflict, Temanggung Tobacco Farmers